APPLICATION OF THE ZOO/PLANKTON INDICATORS FOR ASSESSMENT OF THE NUCLEAR POWER PLANTS IMPACT UPON COOLING POOLS - Dmitriy V. Kulakov (Водное хозяйство России: проблемы, технологии, управление)
The article discusses the outcomes of the researches of zoo/plankton of various type nuclear power plants cooling pools located in different in terms of hydrographic characteristics and zooplankton structure catchment basins. In Koporye Bay, a part of the Bay of Finland water area, discharge of warmed waters of Leningrad Nuclear Power Plant caused the decrease of plankton invertebrates’ quantitative indicators. In the Beloyarsk Nuclear Power Plant cooling pool warming in the most cases was favorable for the zooplankton abundance and biomass increase. In both researched reservoirs the warm water discharge resulted in the decrease of the total species number in the communities. The Neman River (the Baltic Nuclear Power Plant designed receiver for waste waters) in the period of the research was not affected by the nuclear plant impact. As a whole, for this water course water area maximal values of zooplankton abundance and biomass have been registered during spring periods while their decrease has been observed in summer and autumn. The most degree of trophity was noted near towns of Grodno, Kaunas, Yurbarkas and Neman.